Strategies to decolorize high concentrations of methyl orange using growing cells of lactobacillus casei TISTR 1500 - Tantiwa N. (2014)
Batch, fed-batch, and continuous fermentation was used in the processing of methyl orange decolorization using growing cells of Lactobacillus casei TISTR 1500. This report presents the optimal conditions for methyl orange decolorization by the strain TISTR 1500 in modified MRS via a central composite design (CCD) experiment. In particular, the highest decolorization efficiencies were obtained with 13.41 g/L of meat extract, and with 10.89 g/L of yeast extract at pH 6.88 at 35 °C. Under the optimal conditions, the rate of decolorization increased to 322% of that obtained for un-optimized MRS medium. The high concentration of methyl orange (5 g/L) was completely degraded within 9 h in batch fermentation. The total methyl orange load with 8.075 g/L was also decolorized in fed-batch fermentation within 13 h, and the biomass of the strain dramatically decreased after an incubation time of 8 h due to a shortage of sucrose. In the continuous system with a dye-loading rate of 600 mg/L/h and a total of loaded azo dye of 7.2 g/L, high efficiency of methyl orange removal was significantly high, at 98%.